Los poderes innominados de los árbitros - Prato, Enrico del (2018)
This paper refers to the implicit powers of the arbitrators. They are on the same level as the effects of any contract, with the particularity that they are not explicitly provided for by law nor by the parties, but represent natural expressions of the deployed function.